Exploring Teacher's Strategies and Challenges in Enhancing Student’s Critical Thinking Skills in Reading at Mtsn 1 Kota Palangka Raya - Hapsari, Muliana Setia; Qalyubi, Imam; Widiastuty, Hesty (IKIP Siliwangi, 2025)
This study aims to explore the strategies used by English teachers to enhance students' critical thinking skills in reading at MTsN 1 Kota Palangka Raya, an Islamic junior high school in Central Kalimantan. A descriptive qualitative approach with a case study design was employed to gain an in-depth understanding of teaching practices within a real classroom context. Data were collected through classroom observations, interviews, and documentation, and analyzed using thematic analysis. The findings reveal that teachers employed various strategies such as interactive read-alouds, divergent questioning, the SQ3R method, group discussions, and project-based learning. These strategies were often integrated with Islamic values like honesty, responsibility, and deliberation. Despite facing challenges such as students’ low vocabulary and reluctance to express opinions, teachers addressed these through scaffolding, gradual questioning, and differentiated tasks. The study highlights the importance of culturally responsive teaching strategies that align with Islamic values and suggests practical ways to foster critical thinking in madrasah settings.